An analysis of inpatient pediatric sickle cell disease: Incidence, costs, and outcomes. Issue 1 (12th August 2017) - Bou‐Maroun, Laura M.; Meta, Fabien; Hanba, Curtis J.; Campbell, Andrew D.; Yanik, Gregory A.
Abstract: Objective: To identify characteristics of pediatric sickle cell disease (SCD) hospitalizations and to examine admission demographics and medical expenditures. Methods: Admissions with SCD were identified from the 2009 and 2012 releases of the Healthcare and Cost Utilization Project's Kids Inpatient Database. Disease‐specific secondary diagnoses including acute chest syndrome (ACS), vaso‐occlusive pain crisis (VOC), splenic sequestration, and stroke/transient ischemic attack were analyzed for patient and hospital demographics. Analytical endpoints included total healthcare expenditures and mortality. Results: We reviewed 75, 234 inpatient hospitalizations with a diagnosis of SCD. Over $900, 000, 000 was spent annually in associated healthcare expenditure. The median length of hospitalization stay (LOS) for all admissions was 3 days (interquartile range [IQR] 2–5 days). VOC was the most frequent secondary diagnosis, recording 48, 698 total hospitalizations and a median LOS of 3 days (IQR 2–6 days). Of the 8, 490 hospitalizations with ACS, the infant population had a significantly higher mortality rate compared to other age groups (2% vs. 0.3%, P < 0.001). Cerebral vascular accidents incurred the second highest median hospitalization cost ($18, 956), behind ACS ($22, 631). A high proportion of Caucasian patients died during hospitalization for VOC (0.4% vs. 0.1%, P = 0.014) and ACS (4% vs. 0.2%, P < 0.001) when compared to non‐Caucasians. Conclusion: Inpatient hospitalizations for secondary manifestations of pediatric SCD were associated with significant healthcare expenditures. Patients with an increased statistical risk for death during hospitalization included Caucasians with SCD complications of ACS and VOC, and patients <1‐year‐old with ACS. Further research is needed to substantiate the associated clinical significance of these findings.